Research on Lithofacies Paleogeography and Caprock Evaluation of the Middle Cambrian in the Tarim Basin, NW China - Xueqiong Wu; Wei Yang; Dongmei Bo; Tianyu Ji; Caiyuan Dong; Tiansi Luan; Junya Qu (Applied Sciences, 2024)
Cambrian subsalt dolomite is an important strategic area for natural gas exploration in the Tarim Basin. The gypsum-salt rocks, argillaceous mudstone and argillaceous dolomite strata developed in large areas of the Middle Cambrian can be used as good caprocks. The sealing ability and favorable area distribution of the Middle Cambrian caprock in the Tarim Basin are studied through the lithofacies paleogeography and microscopic evaluation of the Middle Cambrian strata in this paper. Based on the 2D seismic interpretation covering the entire basin, combined with data from drilling, outcrops, well logging, core samples and thin sections, the sedimentary characteristics and lithofacies paleogeography of the Middle Cambrian were studied and then the thickness of the Middle Cambrian gypsum-salt rocks, gypsiferous mudstone and gypsiferous dolomite was analyzed in the Tarim Basin. Studies suggest that the Middle Cambrian is primarily characterized by the development of restricted-platform facies. In the Awati Depression, the northern part of the Tazhong Uplift, the southern part of the Manxi Low Uplift, and the central and northern parts of the Bachu Uplift, the thickness of the gypsum-salt rock strata is relatively large. Moreover, centered on the northern part of the Bachu Uplift, the thickness of the gypsum-salt rocks decreases irregularly towards the periphery, forming a circumferential distribution. To investigate the sealing ability of caprocks, 64 core samples from four wells were examined under a microscope, and physical parameters as well as breakthrough-pressure tests were conducted. By establishing correlations between various parameters, the sealing ability of different rock types in the Cambrian formation within the study area was quantitatively assessed. The research suggests that gypsum-salt rocks exhibit superior sealing ability compared to gypsiferous mudstone and gypsiferous dolomite, but factors such as faults and geological conditions of gypsum can influence the sealing performance of caprocks. According to both micro- and macro-scale evaluations of the Cambrian strata in the study area, along with constraints imposed by actual drilling exploration results, a comprehensive evaluation method for assessing caprock sealing ability has been established. The results suggest that the Awat Depression, the western and southern parts of the Manxi Low Uplift, the northern and western parts of the Tazhong Uplift, and the central part of the Tabei Uplift are favorable areas for the development of caprocks.